ANALISIS KEBERHASILAN PENGGUNAAN EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) 4.0 MENGGUNAKAN METODE DELONE AND MCLEAN - Sofiani, Efin; Mulyani, Evi Dewi Sri; Mufizar, Teuku (JRIS : Jurnal Rekayasa Informasi Swadharma, 2025)
The Ministry of Religious Affairs launched the REP-MEQR project to improve primary and secondary education management standards. One of its programs is the Education Management Information System (EMIS) application, a data management platform and data collection centre for schools under the Ministry of Religious Affairs. As a new system, it requires input and feedback, both positive and negative. The DeLone and McLean model is widely used to evaluate information systems. This study analyzes the success of using EMIS by applying the DeLone and McLean model. This quantitative research collects data through questionnaires distributed to 117 MT operators in Ciamis Regency. Data processing was carried out using SPSS and SmartPLS applications. The Descriptive analysis for this research uses a Likert scale to measure user perceptions of the six dimensions of DeLone and McLean in EMIS 4.0. The descriptive analysis states that all research indicators for the six dimensions of DeLone and McLean, namely system quality, information quality, service quality, use, user satisfaction, and net benefits, are rated positively. The hypothesis test was conducted to measure the influence between the variables of the DeLone and McLean dimensions. The research results indicate that not all variables influence other variables. Out of the nine hypotheses, only five were accepted. This research can be used as one of the evaluation materials by the Ministry of Religious Affairs based on the opinions of a small portion of EMIS 4.0 users as input to improve the quality of EMIS 4.0 to become an optimal information system as the central school information system in the Ministry of Religious Affairs.Kementerian Agama meluncurkan proyek REP-MEQR untuk meningkatkan standar pengelolaan pendidikan dasar dan menengah. Salah satu programnya adalah aplikasi Education Management Information System (EMIS) sebagai platform pengelolaan data dan pusat pengumpulan data untuk sekolah di Kementerian Agama. Sebagai sistem baru, sistem ini memerlukan masukan serta umpan balik baik yang bersifat positif maupun negatif.  Metode DeLone and McLean banyak digunakan untuk melakukan evaluasi sistem informasi. Penelitian ini bertujuan untuk melakukan analisis keberhasilan penggunaan EMIS dengan menerapkan metode DeLone and McLean. Penelitian ini bersifat kuantitatif dengan mengumpulkan data melalui kuesioner disebarkan kepada 117 operator MTs se-Kabupaten Ciamis. Pengolahan data menggunakan aplikasi SPSS dan SmartPLS. Analisis deskriptif skala likert untuk mengukur persepsi pengguna terhadap enam dimensi DeLone and McLean pada EMIS 4.0. Analisis deskriptif menyatakan semua indikator penelitian untuk keenam dimensi DeLone and McLean yaitu kualitas sistem, kualitas informasi, kualitas layanan, penggunaan, kepuasan pengguna dan manfaat bersih bernilai baik. Uji hipotesa penelitian dilakukan untuk mengukur pengaruh antar variabel dimensi DeLone and McLean. Hasil penelitian menunjukan bahwa tidak semua variabel mempengaruhi variabel lainnya. Dari sembilan hipotesa, hanya lima hipotesa yang diterima. Penelitian ini dapat dijadikan salah satu bahan evaluasi oleh Kementerian Agama dari pendapat sebagian kecil pengguna EMIS 4.0 sebagai masukan untuk meningkatkan kualitas dari EMIS 4.0 agar menjadi sistem informasi yang optimal sebagai pusat sistem informasi sekolah di Kementerian Agama.